2020
DOI: 10.1002/adsc.201900859
|View full text |Cite
|
Sign up to set email alerts
|

Coinage Metal Complexes of Chiral N‐Heterocyclic Carbene Ligands: Syntheses and Applications in Asymmetric Catalysis

Abstract: Chiral N‐heterocyclic carbenes (NHCs) have become ligands of choice due to their remarkable catalytic activity in organic transformation reactions. Combining the chiral NHC ligand family and coinage metals became a productive area of research. The organometallic chemistry of coinage metals with the chiral N‐heterocyclic carbene (NHC) ligands is reviewed, with a special emphasis on the synthesis, characterization and possible applications obtained. Significant sections are devoted to the various recently develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 173 publications
0
24
0
Order By: Relevance
“…Gold catalysis is one of the most captivating topics in Organic Chemistry [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In recent years, particular attention has been devoted to gold catalyzed CAH bond activations as a strategic tool for the formation of new CAC bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Gold catalysis is one of the most captivating topics in Organic Chemistry [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In recent years, particular attention has been devoted to gold catalyzed CAH bond activations as a strategic tool for the formation of new CAC bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Many reviews, prospectives, highlights and comments covering important aspects of transition metal NHC complexes focusing on one particular aspect such as either olefin metathesis, C−C bond formation, reactivity or biological applications, while several others dealt with the organometallic chemistry of carbene complexes featuring specific concepts have been published. These reviews include catalytic hydrogenation reactions of ruthenium(II)−NHC complexes, [17] Fischer type carbene complexes and their multimetal carbene counterparts, [18] electronic properties of NHC complexes, [19] high oxidation state complexes of NHC ligands, [20] coinage metal chiral NHC complexes, [21] organometallic chemistry of 1,2,3‐triazole derived NHC ligands, [22] gold(I) NHC complexes, [23] F‐block NHC complexes, [24] abnormal mesoionic and remote NHC complexes, [25] so on.…”
Section: Scopementioning
confidence: 99%
“…In previous studies, we showed that the hydroxyamide-functionalized NHC•AgI (NHC = N-heterocyclic carbene) complex 1b , derived from leucine, was a versatile chiral ligand precursor for dual enantioselective control in the CuOTf-catalyzed ACA reaction of a cyclic enone with Et 2 Zn [ 15 , 16 ]. The NHC•AgI complex 1 can be easily synthesized by the well-known Ag 2 O method [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Thus, the treatment of azolium salt (NHC•HI, 4 ) with a 0.5 equiv.…”
Section: Introductionmentioning
confidence: 99%